Sariswara Method as the Ideological Foundation of Children's Art Education - Harpang Yudha Karyawanto; Widodo Widodo; Aris Wahyudi; Agus Cahyono (Universitas Negeri Semarang, 2023)
This article aims to reveal the role of the sariswara method initiated by Ki Hajar Dewantara as an ideology of art education in children. Sariswara is a method of educating children through art to familiarize all beauty by combining the experience of all existing senses, both through hearing, sight, physical movement, and also feelings. This learning method has an impact on the formation of children's character. This research uses a qualitative descriptive approach. Research data were collected through literature studies, interviews, and observations. The results of the study revealed that learning art with the sariswara method can form character strengtheningin children, which includes children being more confident, disciplined, together, understanding ethics and aesthetics, having independence, intelligent, creative.